URGENSI PERLINDUNGAN HUKUM TERHADAP NOTARIS OLEH MAJELIS KEHORMATAN NOTARIS (MKN) DALAM DUGAAN TINDAK PIDANA YANG DILAKUKAN OLEH NOTARIS PADA TINGKAT PENYIDIKAN - Martalena Martalena (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
Notary public is a public official who has the duty and obligation to provide legal services and consultation to the public need. Legal assistance that can be given from a notary isin the form of making an authentic deed or other authority as referred to in Act Number 30 of 2004 concerning Notary Position (Notary Position Law). According to Article 15 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, the criminal law policy regarding the limitation of authority in the investigation of a Notary Public is at the stage of legal formulation governing the authority of the Notary Honorary Council in the process trial of a notary in the case of providing recommendations of approval or rejecting requests from investigators, public prosecutors, or judges to take photocopies of the Minutes of Deed and / or documents attached to the Minutes of Deed or Notary Protocol in Notary Storage.Based on the discussion and analysis, it can be concluded that: 1. Notary Honor Advisory Considerations in providing recommendations to the Police Investigator regarding alleged criminal acts committed by the Notary, in the event that the Notary Honorary Council does not give permission to the police investigator because the consideration of the Notary Honorary Council is not sufficient reason for examine and take the minutes of the deed to the Notary Public, in the event that the Notary Honorary Council gives permission to the police investigator because there is sufficient evidence of a criminal act committed by the Notary Public. 2. Legal protection of the Notary Public on the recommendation of the Notary Honorary Council (MKN) to investigators regarding the alleged criminal act, the position of the Notary Public through the MKN can be carried out repressively because it is related to the application of Article 66 paragraph (1) of the UUJN, namely in giving approval or rejecting requests the investigator who wishes to summon a Notary in the trial process of the existence of the Notary Honorary Council as a legal protection institution for the position of a Notary Public. The legal protection given to a Notary aims to avoid the arbitrary actions of the investigator who wishes to summon a Notary in court.